Aminopropyl-modified silica as cross-linkers of polysiloxane containing γ-chloropropyl groups for preparing heat-curable silicone rubber. (July 2016) - Dong, Fuying; Ma, Depeng; Feng, Shengyu
Abstract: A series of aminopropyl-modified silica (APS) with different amine contents was prepared and, subsequently, used as cross-linkers of polysiloxane containing γ-chloropropyl groups (CPPS) to prepare heat-curable silicone rubber (MCSR). The dispersion of APS in polysiloxane matrix was studied by scanning electron microscopy. The curing characteristics, mechanical and thermal properties of the MCSR were analyzed by a rheometer, mechanical testing and thermal gravimetric analysis (TGA), respectively. The effects of the silica (TS530) content and the molar ratio of APS/CPPS on the curing characteristics were studied. The influence of the amounts of TS530 and APS, and the kind of APS, on the comprehensive mechanical properties of MCSR is discussed. The optimized conditions to prepare MCSR were obtained as follows: the amount of TS530, 55 parts per hundreds of polysiloxane in weight; the molar ratio of [NH]/[γ-chloropropyl], 1.5: 1; and the amount of amino groups on the surface of APS, 0.65 mmol/g. Additionally, TGA results show that MCSR has high thermal stability.